CD8+ T cell epitope-flanking mutations disrupt proteasomal processing of HIV-1 Nef. - Milicic, A; Price, D; Zimbwa, P; Booth, B; Brown, H; Easterbrook, P; Olsen, K; Robinson, N; Gileadi, U; Sewell, A; Cerundolo, V; Phillips, R (2005)
CTL play a critical role in the control of HIV and SIV. However, intrinsic genetic instability enables these immunodeficiency viruses to evade detection by CTL through mutation of targeted antigenic sites. These mutations can impair binding of viral epitopes to the presenting MHC class I molecule or disrupt TCR-mediated recognition. In certain regions of the virus, functional constraints are likely to limit the capacity for variation within epitopes. Mutations elsewhere in the protein, however, might still enable immune escape through effects on Ag processing. In this study, we describe the coincident emergence of three mutations in a highly conserved region of Nef during primary HIV-1 infection. These mutations (R69K, A81G, and H87R) flank the HLA B*35-restricted VY8 epitope and persisted to fixation as the early CTL response to this Ag waned. The variant form of Nef showed a reduced capacity to activate VY8-specific CTL, although protein stability and expression levels were unchanged. This effect was associated with altered processing by the proteasome that caused partial destruction of the VY8 epitope. Our data demonstrate that a variant HIV genotype can significantly impair proteasomal epitope processing and substantiate the concept of immune evasion through diminished Ag generation. These observations also indicate that the scale of viral escape may be significantly underestimated if only intraepitope variation is evaluated.